Pemahaman Nilai Filosofi Banten Suci pada Masyarakat Desa Kukuh, Kecamatan Kerambitan, Kabupaten Tabanan - Wulandari, Ida Ayu Gde; Selasih, Ni Nengah (Satya Widya: Jurnal Studi Agama, 2023)
Apart from being known as the island of a thousand temples, Bali is also known as the island of banten. In the story of Rsi Markandeya's journey, it is explained that if you want to survive in Bali, we must carry out a yadnya ceremony. Yadnya is a sincere sacrifice, which in its division consists of five types of yadnya, namely Dewa Yadnya, Manusa Yadnya, Rsi Yadnya, Pitra Yadnya, and Bhuta Yadnya. Banten suci is one type of offering or ceremony which is a symbol of the divine weapon of nawasanga. The public's understanding of banten suci, both in terms of form and philosophy, is still common. People know more about forms without knowing clearly the meaning or philosophy of the sacred offerings. The method used in this study was an open questionnaire at the end of the presentation by the presenter to find out the understanding of the people of Kutuh Village, Kerambitan District, Tabanan Regency regarding the philosophy of banten suci. The conclusion of this paper is that the people of Kutuh Village, Kerambitan District, Tabanan Regency understand well the things delivered by the presenter, especially on the philosophical values ​​of banten suci.